Insights into the molecular underlying mechanisms and therapeutic potential of endoplasmic reticulum stress in sensorineural hearing loss - Li, Guanzhen; Yang, Huiming; Zhang, Peiyuan; Guo, Yan; Yuan, Lili; Xu, Shujiao; Yuan, Yingxue; Xiong, Huabao; Yin, Haiyan (Frontiers in Molecular Neuroscience, 2024)
Sensorineural hearing loss (SNHL) is characterized by a compromised cochlear perception of sound waves. Major risk factors for SNHL include genetic mutations, exposure to noise, ototoxic medications, and the aging process. Previous research has demonstrated that inflammation, oxidative stress, apoptosis, and autophagy, which are detrimental to inner ear cells, contribute to the pathogenesis of SNHL; however, the precise mechanisms remain inadequately understood. The endoplasmic reticulum (ER) plays a key role in various cellular processes, including protein synthesis, folding, lipid synthesis, cellular calcium and redox homeostasis, and its homeostatic balance is essential to maintain normal cellular function. Accumulation of unfolded or misfolded proteins in the ER leads to endoplasmic reticulum stress (ERS) and activates the unfolded protein response (UPR) signaling pathway. The adaptive UPR has the potential to reestablish protein homeostasis, whereas the maladaptive UPR, associated with inflammation, oxidative stress, apoptosis, and autophagy, can lead to cellular damage and death. Recent evidence increasingly supports the notion that ERS-mediated cellular damage responses play a crucial role in the initiation and progression of various SNHLs. This article reviews the research advancements on ERS in SNHL, with the aim of elucidating molecular biological mechanisms underlying ERS in SNHL and providing novel insights for the treatment.